Characterization of Gamma-Secretase-Mediated Cleavage of Receptor Tyrosine Kinases - Merilahti, Johannes (fi=Turun yliopisto|en=University of Turku|, 2021)
ABSTRACT Receptor tyrosine kinases (RTK) are a family of cell surface receptors consisting of 55 members. RTKs regulate intracellular signaling pathways that control fundamental cellular processes including differentiation, proliferation, and survival. The functionality of RTKs is necessary for the development and homeostasis of many tissues. In human pathologies, such as cancer, aberrant RTK signaling is a common feature. Gamma-secretase-mediated regulated intramembrane proteolysis is a proteolytic cleavage of RTKs in two sequential proteolytic events: a sheddasemediated ectodomain shedding followed by the release of a soluble intracellular domain by a gamma-secretase cleavage. The aims of my thesis were to characterize the gamma-secretase-mediated cleavage of RTKs, with a focus on identifying the prevalence of cleavage among RTKs and developing novel methods to identify signaling pathways associated with the process. The results of this thesis indicate that at least half of the RTKs are subjected to gamma-secretase cleavage. In total, 12 new gamma-secretase targets were identified. Many of the identified new gamma-secretase target RTKs, for example AXL and TYRO3, presented cleavage-dependent effect on cell growth. My research also demonstrated that the signaling of TYRO3 full-length receptor and soluble intracellular domain of TYRO3 is different as observed with our novel systems biology methods. Together, these findings represent for a first time an approach to determine the prevalence of gamma-secretase cleavage among RTKs. Moreover, this study presents novel methods and tools for identifying still largely unknown RTK cleavage associated signaling pathways. The RTK processing via proteolytical cleavage has indications for the functionality of RTKs in both normal tissues and cancer. The results of this thesis can provide new insights into the regulation of the functions of RTKs and can be used to develop new strategies to treat cancers. KEYWORDS: receptor tyrosine kinase, RTK, gamma-secretase, regulated intramembrane proteolysis, intracellular kinase domain, shedding, proteomics

TIIVISTELMÄ Ihmisen genomi sisältää 55 reseptorityrosiinikinaasia (RTK). RTK:t ovat solukalvolla sijaitsevia signalointiproteiineja. RTK:t signaloivat solunsisäisten signalointireittien välityksellä ja säätelevät elintärkeitä solutapahtumia, kuten solujen lisääntymistä, erilaistumista ja selviytymistä. RTK ovat tärkeitä monien kudosten kehittymisessä, ja niiden epänormaalia toimintaa on todettu monissa sairauksissa, kuten syövissä. Gamma-sekretaasivälitteinen säädelty solukalvonsisäinen proteolyysi on mekanismi, jolla RTK:t katkaistaan proteolyyttisesti. Tämä on kaksivaiheinen tapahtuma. RTK:n solunulkoinen domeeni katkaistaan ensin ADAM-nimisten proteiinien toimesta ja tätä seuraa gamma-sekretaasin tekemä solukalvon sisäisen osan irrottaminen solukalvolta. Tämän väitöskirjan tavoitteena oli karakterisoida RTK:iden gamma-sekretaasikatkeamista. RTK:iden katkeamisen yleisyyden selvittäminen, sekä menetelmien kehitys, joilla paremmin pystytään tunnistamaan RTK:iden katkeamiseen liittyvää signalointia, olivat tarkemman tutkimuksen kohteena. Selvitimme, että puolet ihmisen RTK:ista on kohteena gamma-sekretaasi-välitteiselle katkaisulle ja tunnistimme yhteensä 12 uutta kohdetta. TYRO3 ja AXL RTK:iden kohdalla solujen kasvun lisääntyminen liittyi näiden RTK:iden katkeamiseen. Lisäksi väitöskirjatutkimuksessani pystyimme osoittamaan, että TYRO3 RTK:n katkeamisesta muodostuvan liukoisen osan aikaansaama signalointi eroaa merkittävästi kokopitkän TYRO3:n aikaansaamasta signaloinnista. Tutkimuksessa tehdyt havainnot osoittavat, että RTK:iden katkeaminen on yleistä ja uudenlaiset analysointimenetelmät auttavat aikaisempaa paremmin tunnistamaan uusia signalointireittejä katkeaville RTK:ille. Tutkimuksen tulokset RTK:iden katkeamisesta sekä sen signaloinnista laajentavat ymmärrystämme RTK:iden signaloinnista ja tulosten antamaa tietoa voidaan käyttää uusien syöpähoitojen kehittämisessä. AVAINSANAT: reseptorityrosiinikinaasi, RTK, gamma-sekretaasi, säädelty solukalvonsisäinen proteolyysi, solunsisäinen kinaasidomeeni, proteomiikka.